An Appraisal of President Muhammadu Buhari’s Strategic Silence on Selected National Issues and Its Implication on His Government’s Image - Andrew Asan Ate; Obinna Johnkennedy Chukwu; Jamila Abubakar Dauda (Randwick International of Social Science Journal, 2021)
This study examines the strategic silence under President Muhammadu Buhari’s administration in Nigeria. Anchored on Shannon and Weaver mathematical model of communication and spiral of silence theory, the study beams a searchlight on instances of President Buhari’s strategic silence, public perception of Buhari’s silence on sensitive national issues; and the implications of his silence on his administration’s image. The study which adopted qualitative research approach recommends that President Muhammadu Buhari should personally cultivate the culture of addressing Nigerians on sensitive national issues to give the people a sense of belonging and trust and that the president should change the negative perception of his administration by reducing the rate at which he depends on media team and spokespersons to communicate to the people on virtually everything.